A Review of Flax Fiber Reinforced Thermoset Polymer Composites: Thermal-Physical Properties, Improvements and Application - Malik, K. (Taylor and Francis Ltd., 2021)
Flax is the strongest natural fiber used as reinforcement for polymer-based composites due to its ecological properties, low specific gravity, renewability, biodegradability, recyclability besides its high mechanical properties. However, thermal properties of flax fibers depend on its chemical composition and structure, so it should be carefully controlled during the production process of composites, which affect the final product performance. A review of flax fiber-reinforced thermoset composites (FRTCs) and their hybrids is presented in the article, mainly focus on thermal performance, water absorption, and durability of the composites. The effects of filler materials hybridization and fiberâs chemical modification on the properties and performance of the FRTCs are also covered. Finally, key industrial applications and future possible research work based on the current understanding of FRTCs, and their hybrids also are addressed. Â© 2021 Taylor & Francis.